On correction and improvement of professional Ukrainian language of the teachers (New Collegium, 2020)
The article addresses the need for special efforts to resolve the issue of correction of teachers' professional Ukrainian language in the bilingual and Russian-speaking regions of Ukraine. The article also provides the materials to prevent and overcome the widespread language mistakes of the teachers. The most widespread phonetic and orthoepic mistakes in the professional speech of a teacher are considered, namely: incorrect pronunciation of words, incorrect pronunciation of certain Ukrainian sounds and sound combinations, stunning of the consonants in the absolute end of the word and in the middle of the word before the deaf, etc. in Ukrainian words. The causes and types of lexical mistakes in teacher's speech are illustrated. There is a large number of dangerous phrases from the point of view of teachers and students observing the correct language. The most common grammatical mistakes are emphasized, namely: absence of an exclamation mark for the students' names when addressing them, incorrect spelling of Ukrainian masculine surnames, inattention to differences in management of word combinations etc. The teacher must have a good command of the scientific terms of those subjects, which he teaches the basics, as well as the peculiarities of Ukrainian scientific style constructions. The article describes the numerous Ukrainian designs of the scientific style, which are used daily by the teacher in his professional speech and in which mistakes are often made. The article concludes the importance of optimizing the teaching of professional speech to students-future teachers, as well as the need to organize work on the correction of speech in special training courses and advanced training of current teachers. The materials offered in the article can be used (with some correction) in the system of speech training of teachers-teachers of different specialties at all faculties of pedagogical colleges.